Pattern and Features of Pediatric Endocrinology Referrals: A Retrospective Study in a Single Tertiary Center in Italy - Bellotto, Eleonora; Monasta, Lorenzo; Pellegrin, Maria Chiara; Bossini, Benedetta; Tamaro, Gianluca; Conte, Maria Sole; Faleschini, Elena; Barbi, Egidio; Tornese, Gianluca (Frontiers in Pediatrics, 2020)
Introduction: The knowledge of the pattern and the features of paediatric endocrinology referrals is crucial to optimize resources and guide public health interventions. We explored the numbers and the reasons for referral to a paediatric endocrinology outpatient clinic and investigated their features in terms of assignment of priority ranks, sex, age differences, the prevalence of pathological findings among referred cases, and the agreement among referrals, final diagnosis, treatment, and follow-up. Methods: Retrospective study with data collection for paediatric endocrinology first visits between November 2012 and February 2019 in a tertiary centre. Results: A total of 1930 first visits were performed with an overall number of referrals of 2165, and an increasing trend over the years. The most frequent referral reasons were slow growth, precocious puberty, and obesity; 14% of visits were classified as “urgent” (<7 days), 35% as “deferrable” (<30 days), and 51% as “planned” (<180 days). Sex and age differences among referrals were detected, with criticality in the appropriate timing for referral. Thirty-eight percent of patients had pathological findings. In 4% of the cases the final diagnosis was not concordant with the reason for referral. Treatment was prescribed in 35% of cases, and 67% returned at least for one follow-up visit. Conclusion: The study highlighted the need to target medical education of primary care on the definition of priority ranks, the need for more extended observation periods for subclinical or para-physiological conditions, the appropriate timing for referral, based on the definition of conditions or the best window of intervention.